175 A model for participant engagement in research: the MS register. Issue 12 (14th November 2019) - Middleton, R; Allen-Philbey, K; Schmierer, K; Espasandin, M; Roberts, C; Nicholas, R; Rodgers, J; Lockhart-Jones, H; Tuite-Dalton, K; Ford, DV
Abstract : Objectives: Increase people with MS (PwMS) engagement with research and provide increased utility to PwMS/Clinicians. Background: The UK MS Register (UKMSR) was established by the MS Society to collect research and service provision data. We have now collected 8 years of Patient Reported Outcome (PRO) data from PwMS, with more than 300, 000 responses, thus far with little feedback given to participants. Methods: We report our first experience providing feedback to PwMS, Patient Public Involvement (PPI) was utilised to better design data collection and feedback instruments. Gathered responses from UKMSR users by email/phone. Focus groups with clinicians and PwMS at Barts Health NHS Trust. Output: Comprehensive feedback should be accessible for all that opt-in. Results: The website was re-designed to graph core instruments and provide a comprehensive 'feedback report' for screen/print. All participants were contacted, 5596 logged-in. 4819 existing, 773 were new users. 1291 declined feedback. Discussion: Allowing feedback clearly addresses unmet needs. The increased completions of questionnaires after re-launch suggests PwMS are more engaged with research. We will carry out further research in exploring PwMS satisfaction with the new format and on the volume and depth of data. Conclusion: Allowing participants to review their own detailed feedback to questionnaires facilitates increased engagement with research.